Toxinology in Colombia: contributions of ophidism/scorpionism program and other research groups (2019)
ABSTRACT: Background: Toxinology is a sub-field of toxicology dedicated to studying toxins produced by animals, plants and, microorganisms. In Colombia, during the last thirty years, this area has been mainly investigated by Ophidism/Scorpionism Program of Universidad de Antioquia. However, some other research groups have also contributed to our knowledge of venoms and toxins, as well as their related effects and treatments. Objective: to highlight the most significant findings in toxinology made by the Ophidism/Scorpionism Program and other research groups in Colombia. Methods: 119 papers dealing with the history of ophidiology and toxinology in Colombia were collected and analyzed. Results: some useful terms are described to understand toxinology and its scope. Also, a brief history of ophidiology is presented, spanning from the discovery of America until present-day findings. Finally, an overall description of several results related to toxin isolation, characterization, antivenoms, clinical trials, description of new species, proteomic and transcriptomic, among others. The nineteens were characterized by the study of snakebites, their clinic manifestations, and the use of antivenoms. In addition, the ethnopharmacological studies of medicinal plants used in snakebite treatments began to be explored. The 2000s included the newly ethnopharmacology, toxin isolation, clinical trials, inhibitor studies, scorpion venom characterization, and scorpion stings features. Finally, from 2010 until today, proteomic and transcriptomic gave the most important findings. Conclusions: Toxinology works in Colombia have contributed to our knowledge about endemic species, clinical manifestations of snakebite and scorpion stings, and the development of new therapeutic agents. However, we invite Colciencias and other funding agencies to assign more resources to support a higher number of researchers in this field, since snakebite is considered a neglected tropical disease by the World Health Organization, which needs more attention from governments and scholars. Finally, the venoms of some species and their possible mode of action are still unknown to us. Besides, given the complexity of venoms, we are not yet aware of the potential use of toxins in current biomedicine. Thus, studies in toxinology must continue.